Hockey for fun! - Will, Sandra (Minneapolis : Compass Point Books, 2004)
Describes the sport of hockey and presents information on the basic equipment, different moves, scoring, rules and more.
Includes bibliographical references (p. 47) and index.
4.4
3-6
Keywords: Hockey -- Juvenile literature; Hockey; Hockey